2014
DOI: 10.1021/ed4003578
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceptions about the Use of Educational Games as a Tool for Teaching the Periodic Table of Elements at the High School Level

Abstract: The study reported here was conducted to investigate the perceptions of high school students on the use of educational games as a tool for teaching the periodic table of elements in a chemistry class in Spain. The 127 students who participated in this study came from six different classes in grade 10 (15−16 years old). The students' perceptions of the usefulness of a series of 13 specifically designed games as educational tools was assessed. This was achieved in a survey containing 13 items using a 5point Like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 32 publications
3
57
0
11
Order By: Relevance
“…These games provided an enjoyable way for students/teachers to work together in groups and enabled learning to arise from playing the game. These findings are in agreement with other studies which have confirmed that educational games improve students' motivation, raise interest of the subject and contribute to the development of positive perceptions toward science (Costa, 2007;Franco-Mariscal, Oliva-Martínez, & Gil, 2015;Koballa, 1988). Orlik et al (2005) found the use of games to be one of the most important approaches in the teaching of chemistry.…”
Section: Resultssupporting
confidence: 90%
“…These games provided an enjoyable way for students/teachers to work together in groups and enabled learning to arise from playing the game. These findings are in agreement with other studies which have confirmed that educational games improve students' motivation, raise interest of the subject and contribute to the development of positive perceptions toward science (Costa, 2007;Franco-Mariscal, Oliva-Martínez, & Gil, 2015;Koballa, 1988). Orlik et al (2005) found the use of games to be one of the most important approaches in the teaching of chemistry.…”
Section: Resultssupporting
confidence: 90%
“…Para ello, probamos dicho juego original con alumnos de Educación Infantil en dos ocasiones y lo sometimos a sendas evaluaciones. En la literatura pueden encontrarse ejemplos en los que el juego se ha aplicado con éxito a la enseñanza y el aprendizaje de las ciencias en todas las etapas educativas, incluida la Educación Superior (Cabra, 2004;Franco-Mariscal, Oliva-Martínez y Almoraim, 2014;Giménez, Pagés y Martínez, 2011;Muñoz, 2010;Noy, 2011;Rodríguez, 2007;Uría, 2004).…”
Section: Introductionunclassified
“…Para ello, probamos dicho juego original con alumnos de Educación Infantil en dos ocasiones y lo sometimos a sendas evaluaciones. En la literatura pueden encontrarse ejemplos en los que el juego se ha aplicado con éxito a la enseñanza y el aprendizaje de las ciencias en todas las etapas educativas, incluida la Educación Superior (Cabra, 2004;Franco-Mariscal, Oliva-Martínez y Almoraim, 2014;Giménez, Pagés y Martínez, 2011;Muñoz, 2010;Noy, 2011;Rodríguez, 2007;Uría, 2004). 1 Se utilizará el género masculino para hacer referencia a ambos sexos como grupo de población, con la finalidad de facilitar la lectura y la redacción, sin intención de discriminación, ni de uso sexista del lenguaje 374 Revista Eureka sobre Enseñanza y Divulgación de las Ciencias 13 (2), [373][374][375][376][377][378][379][380][381][382][383] 2016 EXPERIENCIAS, RECURSOS Y OTROS TRABAJOS En nuestro trabajo combinamos juego, educación matemática y científica, ingredientes que se rebelan idóneos para la formación de futuros docentes (Fernández-Oliveras y Oliveras, 2014a, 2014b, 2015.…”
unclassified
“…Several board games for supporting the teaching of chemistry courses have been employed by many schoolteachers and science education scholars [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Research shows the difficulties in helping students achieve higher learning motivation by using only the traditional modes of memorization and repeated practice, which may cause students to lose their interest in science as well as their willingness to further study and explore science independently [2,3]. It is evident that using board games for teaching can improve students' motivation for learning, reduce the learning difficulty of complex concepts, and subsequently improve their learning efficiency [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%